A comparative evaluation of the influence of three different vehicles on the antimicrobial efficacy of triple antibiotic paste against Enterococcus faecalis: An In vitro study - Shouvik S Mandal; Sumanthini V Margasahayam; Vanitha U Shenoy (Wolters Kluwer Medknow Publications, 2020)
Introduction: The root canal is a hub of numerous microorganisms. Routine endodontic procedures fail to remove the resistant microorganisms such as Enterococcus faecalis. Aim: The aim of the present study was to evaluate the influence of different vehicles on the antimicrobial efficacy of triple antibiotic paste (TAP) on E. faecalis infected root canals. Materials and Methods: Eighty single-rooted and freshly extracted human teeth were prepared in radicular portion, and pure culture of E. faecalis (ATCC® 29212™) inoculum was injected into canals of tooth blocks and incubated for 21 days. Tooth blocks were divided into five groups. Each experimental group was then medicated with 0.1 ml of TAP and no medication was added for control groups. After 21 days of incubation at 37°C, colony-forming units per milliliter (CFU/ml) were counted for each group. Results: Group II treated with TAP mixed with propylene glycol revealed a maximum reduction in CFU/ml, and that was followed by Group I and Group III, where TAP was mixed with 2% chlorhexidine (CHX) and 0.9% normal saline, respectively. Data were compared and analyzed using statistics software. The results were considered statistically significant for P < 0.05. There was a statistically significant difference in CFU/ml between propylene glycol and positive control group, between CHX and positive control group, between saline and positive control group. Conclusions: The propylene glycol group with TAP was the most effective vehicle for the elimination of E. faecalis from canals of tooth blocks, followed by 2% CHX solution as the second vehicle of choice over 0.9% normal saline.